2020
DOI: 10.1038/s41598-020-65058-1
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Compostable Coffee Pods: A US University Based Case Study

Abstract: Single-serve machines have proven to be a rapid and convenient mechanism for preparing coffee for consumption. However, disposing the single-use coffee pods accompanying each use creates insurmountable waste in landfills. With the introduction of biobased products being certified as industrially compostable, there is scope for an effective waste stream for nearly all biobased products that avoids adding to landfills. The case presented in this paper demonstrates the success of composting compostable coffee pod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…These studies highlighted how the capsule system does not have an exceptionally greater environmental impact than the two conventional systems and how energy consumption (and consumer habits) has a strong impact in determining performance. Kooduvalli et al 32 examine the effectiveness of composting compostable coffee pods within a local industrial‐scale composting facility applying the LCA approach. Their comparison to conventional plastic coffee pods demonstrates the benefits of compostable coffee pods (reduced composting time and reduced costs of waste disposal).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies highlighted how the capsule system does not have an exceptionally greater environmental impact than the two conventional systems and how energy consumption (and consumer habits) has a strong impact in determining performance. Kooduvalli et al 32 examine the effectiveness of composting compostable coffee pods within a local industrial‐scale composting facility applying the LCA approach. Their comparison to conventional plastic coffee pods demonstrates the benefits of compostable coffee pods (reduced composting time and reduced costs of waste disposal).…”
Section: Resultsmentioning
confidence: 99%
“…• Water vapour seems to have the largest impact on the metal yield Kooduvalli et al 32 • Need to evaluate different impacts to get an accurate assessment • From the combination of lower impacts related to composting and lower costs in terms of net purchase and disposal showing cost savings of up to 21%.…”
Section: Study Key Messagesmentioning
confidence: 99%
“…Solvolysis can also be conducted without a catalyst [10]. Studies have shown that the tensile strength and modulus of single fiber filaments can be retained to 100% of virgin properties [10,13]. For this paper, the supercritical solvolysis process with a batch-type reactor is considered.…”
Section: Solvolysis Processmentioning
confidence: 99%
“…With respect to solvolysis, solvents related to the supercritical process have been considered. Additionally, the overall reduction in EE from one generation to the next is demonstrated using the cut-off approach [12,13]. This helps determine the change in EE within the product from one generation to the next.…”
Section: Scope Of the Current Studymentioning
confidence: 99%
See 1 more Smart Citation